2016
DOI: 10.1007/s10342-016-0937-z
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific and generic biomass equations for seedlings and saplings of European tree species

Abstract: Biomass equations are a helpful tool to estimate the tree and stand biomass production and standing stock. Such estimations are of great interest for science but also of great importance for global reports on the carbon cycle and the global climate system. Even though there are various collections and generic meta-analyses available with biomass equations for mature trees, reports on biomass equations for juvenile trees (seedlings and saplings) are mainly missing. Against the background of an increasing amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 48 publications
(61 reference statements)
3
59
3
1
Order By: Relevance
“…Dendrochronological studies revealed mean radial increments of 1.27 and 1.59 mm/year, according to two chronologies from western Poland (Cedro & Nowak, 2015). In Europe, biomass of Q. rubra is assessed using allometric models and biomass expansion factors developed for Q. robur (Forrester et al, 2017; Teobaldelli, Somogyi, Migliavacca, & Usoltsev, 2009), with the exception of young trees, where biomass may be estimated from root collar diameter (Annighöfer et al, 2016; Dyderski & Jagodziński, 2018a; Jagodziński, Dyderski, et al, 2018). In the United States, models for biomass and volume calculations were provided by Gower, Reich, and Son (1993) and Martin, Kloeppel, Schaefer, Kimbler, and McNulty (1998).…”
Section: Response To Environmentmentioning
confidence: 99%
“…Dendrochronological studies revealed mean radial increments of 1.27 and 1.59 mm/year, according to two chronologies from western Poland (Cedro & Nowak, 2015). In Europe, biomass of Q. rubra is assessed using allometric models and biomass expansion factors developed for Q. robur (Forrester et al, 2017; Teobaldelli, Somogyi, Migliavacca, & Usoltsev, 2009), with the exception of young trees, where biomass may be estimated from root collar diameter (Annighöfer et al, 2016; Dyderski & Jagodziński, 2018a; Jagodziński, Dyderski, et al, 2018). In the United States, models for biomass and volume calculations were provided by Gower, Reich, and Son (1993) and Martin, Kloeppel, Schaefer, Kimbler, and McNulty (1998).…”
Section: Response To Environmentmentioning
confidence: 99%
“…All regressions were undertaken using natural logarithmic transformation (Equation (4)) of the tree dimensions, in line with previous work done by Pretzsch et al [56], Böhm et al [20], Annighöfer et al [34,42], and Stankova et al [35]:…”
Section: Statistical Analysis Allometric Modelling and Total Biomassmentioning
confidence: 99%
“…Compared to our equation, the differences at RCD 10 cm were 15.0 kg per tree which probably reflects the different stature of trees under differing stand densities. The study by Annighöfer et al [42] analyzed seedlings of 19 tree species, including Robinia pseudoacacia L. (n = 238). Compared to our study, there is a difference of 1.3 kg per tree for a RCD of 3.0 cm.…”
Section: Correlation Of Stand Parameter and Allometric Biomass Modelsmentioning
confidence: 99%
See 2 more Smart Citations